Effects of fasted vs fed-state exercise on performance and post-exercise metabolism: A systematic review and meta-analysis - Aird, T. P.; Davies, R. W.; Carson, B. P. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The effects of nutrition on exercise metabolism and performance remain an important topic among sports scientists, clinical, and athletic populations. Recently, fasted exercise has garnered interest as a beneficial stimulus which induces superior metabolic adaptations to fed exercise in key peripheral tissues. Conversely, pre-exercise feeding augments exercise performance compared with fasting conditions. Given these seemingly divergent effects on performance and metabolism, an appraisal of the literature is warranted. This review determined the effects of fasting vs pre-exercise feeding on continuous aerobic and anaerobic or intermittent exercise performance, and post-exercise metabolic adaptations. A search was performed using the MEDLINE and PubMed search engines. The literature search identified 46 studies meeting the relevant inclusion criteria. The Delphi list was used to assess study quality. A meta-analysis and meta-regression were performed where appropriate. Findings indicated that pre-exercise feeding enhanced prolonged (P = .012), but not shorter duration aerobic exercise performance (P = .687). Fasted exercise increased post-exercise circulating FFAs (P = .023) compared to fed exercise. It is evidenced that pre-exercise feeding blunted signaling in skeletal muscle and adipose tissue implicated in regulating components of metabolism, including mitochondrial adaptation and substrate utilization. This review's findings support the hypothesis that the fasted and fed conditions can divergently influence exercise metabolism and performance. Pre-exercise feeding bolsters prolonged aerobic performance, while seminal evidence highlights potential beneficial metabolic adaptations that fasted exercise may induce in peripheral tissues. However, further research is required to fully elucidate the acute and chronic physiological adaptations to fasted vs fed exercise.